THE REPRESENTATION OF MALE FIGURES IN 1969MARLBORO AND 1956 LUCKY STRIKE PRINTED ADVERTISEMENT - Razan, Nur Ainina (LANTERN (Journal on English Language, Culture and Literature), 2016)
Nowadays, people are getting consumptive because of impact ofadvertisements. Most of them do not know that the advertisements can changetheir perceptions toward a product. The product which is less popular before canrise highly because of attractive promotion derived by the advertisements. In theadvertisements, audiences are given not only the product’s information, but alsobrand image represented by a figure. In Marlboro advertisement published on July 25, 1969 in Time Magazineand Lucky Strike advertisement published on 1956 in TV Radio Mirror MagazineVol. 46 No. 1, for example, the figure shown is a man or men as genderpreference of the marketing target. However, each advertisement have differentconcept which leads into a more specific marketing target. From the analysisusing semiotics theory, it can be concluded that Marlboro is directed to maleaudiences who like freedom and nature while Lucky Strike is directed to maleaudiences whose lives cannot be separated from women and money. Thus, it givesdifferent images of both brands. Marlboro has an image of macho while LuckyStrike has an image of rich and romantic.